Standalone Point-of-Use Device for Gluten Detection in Food: POCT Application Experiment in SMARTER-SI European Project - Jorge Elizalde; Xabier Eguiluz; Kepa Mayora; Luis Alfonso Rivas; Antonio Sanz; Jan Dehnert; Vadim Goridko; Stefan Görlandt; Martin Schädel (Proceedings, 2017)
In this work, we present an automatic and standalone microfluidic-based immunosensor to detect food allergens for food safety. The system has been developed as an application experiment in the SMARTER-SI European project. It comprises a microfluidic cartridge fabricated in cyclic olefin polymer by injection molding, the fluidic components to drive the reagents, two alternative optical detection systems based on fluorescent or colorimetric detection, respectively, and the electronics to manage all the components. As a proof-of-concept, gluten was immunodetected in a sandwich format by using R5 monoclonal antibody as capturing and detector probe. Gluten -antibody binding was revealed by using R5 mAb labelled to Alexa Fluor 647 or conjugated to horseradish peroxidase (HRP) for the fluorescence or the colorimetric version, respectively。